SOSIALISASI PENERAPAN NILAI – NILAI PANCASILA SILA KE-3 BAGI GENERASI “Z” - Dian Wahyudin; Ana Chaerunisyah; Indriani Rahayu Ning Tyas; Faizah Julina; Mercy Spesa Devina de Fretes (Gapenas Publisher, 2023)
Pancasila, as the foundation of the Indonesian state, emphasizes the importance of applying moral and ethical values in community life. One of the values that is highly relevant to emphasize is the Third Principle, which is